VoicePedia: Towards Speech-based Access to Unstructured Information - Sherwani, J.; Yu, Dong; Paek, Tim; Czerwinski, Mary; Ju, Yun-Cheng; Acero, Alex; Ju, Y. C. (Interspeech, 2007)
Currently there are no dialog systems that enable purely voice-based access to the unstructured information on websites such as Wikipedia. Such systems could be revolutionary for non-literate users in the developing world. To investigate interface issues in such a system, we developed VoicePedia, a telephone-based dialog system for searching and browsing Wikipedia. In this paper, we present the system, as well as a user study comparing the use of VoicePedia to SmartPedia, a Smartphone GUI-based alternative. Keyword entry through the voice interface was significantly faster, while search result navigation, and page browsing were significantly slower. Although users preferred the GUI-based interface, task success rates between both systems were comparable – a promising result for regions where Smartphones and data plans are not viable. Index Terms: dialog system, information access